Deviations of the Light Distribution from the Sersic's model in Elliptical galaxies - Omar Saleh; Saad Youins (مجلة التربية والعلم, 1999)
Abstract: The surface brightness profiles of 46 elliptical galaxies, belong to Coma Cluster of galaxies have been fitted by the generalized Sersic r1/n – law for the intermediate radius range . The mean deviations between the adopted model and the surface brightness profiles of the galaxies found to be less than (0.03) mag arcsec-2. The deviation profiles between the observations and the adopted models show that the maximum negative deviation found to be around the reduced radius of 0.86, while the maximum positive deviation were found to be around the reduced radius of 0.96. The crossing points between the adopted models and the observed surface brightness profiles were found to be around the reduced radius 0.65, 0.83 and 1.0.